A 27‐year‐old female presented with diffuse alveolar haemorrhage due to breast angiosarcoma with lung metastasis. Issue 5 (25th March 2019) - Lee, Po‐Hsin; Chen, Yun‐An; Fu, Pin‐Kuei
Abstract : Angiosarcomas are rare soft‐tissue sarcomas of endothelial cell origin and have a poor prognosis. Diffuse alveolar haemorrhage (DAH) is a syndrome characterized by the accumulation of intra‐alveolar red blood cells. However, neoplastic diseases are not commonly considered in the differential diagnosis of DAH. We report a case of a 27‐year‐old female with the diagnosis of primary breast angiosarcoma developing DAH. This raised our concern that angiosarcoma with lung metastasis may present with DAH and should be considered as an important fatal differential diagnosis of DAH. Abstract : We report a case of a 27‐year‐old female with the diagnosis of primary breast angiosarcoma developing DAH. This raised our concern that angiosarcoma with lung metastasis may present with diffuse alveolar haemorrhage (DAH) and should be considered as an important fatal differential diagnosis of DAH.